DESIGN AND CONSTRUCTION TECHNIQUE FOR LOW EMBODIED ENERGY BUILDING: AN ANALYTICAL NETWORK PROCESS APPROACH - Haruna, Abdulrahman; Shafiq, Nasir; Ali, Montasir Osman; Mohammed, Musa; Haruna, Sani (Journal of Engineering and Technological Sciences, 2020)
Energy performance in the construction industry is one of the significant features to be assessed in order to achieve sustainability in the built environment. There is a limited amount of literature on the analytical network process (ANP) in achieving sustainability towards reducing embodied energy. The aim of this study was to achieve buildings with less embodied energy through design, construction techniques and automation using ANP in order to promote sustainable construction. Data collection was primarily done by way of a well-structured questionnaire and an expert opinion survey. The responses retrieved from the questionnaire were analyzed using descriptive statistics and ranked accordingly. An ANP model was developed using multi-criteria decision-making based on the expert survey and used to prioritize and assign an important weighting for the identified criteria. The findings showed that multi-criteria decision-making with ANP when effectively employed will help in achieving sustainable buildings with low embodied energy. Reducing the amount of cement through design and building information modeling is the most significant factor towards achieving buildings with less embodied energy.